Serum Marker Score Based on Prognostic Nutrition Index, Carcinoembryonic Antigen, and Carbohydrate Antigen 19-9 Is Associated With Recurrence for Patients Undergoing Surgery for Pancreatic Ductal Adenocarcinoma. Issue 9 (October 2018) - Nakagawa, Shigeki; Yamashita, Yo-ichi; Umezaki, Naoki; Yamao, Takanobu; Okabe, Hirohisa; Imai, Katsunori; Nitta, Hidetoshi; Hashimoto, Daisuke; Chikamoto, Akira; Baba, Hideo
Abstract : Objectives: The prognostic value of the prognostic nutrition index (PNI) in pancreatic ductal adenocarcinoma (PDAC) is still controversial. This study aimed to assess the correlation between PNI and the outcome for PDAC patients and to generate a new score from PNI and serum markers. Methods: This study investigated 151 patients who underwent pancreatic resection for PDAC between April 2002 and June 2012. Disease-free survival (DFS), overall survival, and clinicopathological parameters were analyzed according to the PNI value. Results: The low PNI patients had poorer 5-year DFS rate than high-PNI patients (10.7% and 34.8%, respectively). Multivariate analyses revealed that independent risk factors for poor DFS were high carcinoembryonic antigen (hazard ratio [HR], 1.53; P = 0.038), high carbohydrate antigen 19-9 (HR, 1.67; P = 0.017), positive lymph node metastasis (HR, 1.98; P = 0.017), R1 or 2 resection (HR, 3.50; P < 0.001), and low PNI (HR, 0.37 [high/low]; P = 0.029]. Scoring based on the formula −0.49 × (PNI) + 0.41 × (carcinoembryonic antigen) + 0.67 × (carbohydrate antigen 19-9) was significantly associated with poor DFS ( P < 0.001) and overall survival ( P = 0.0019). Conclusions: Low PNI and serum marker score are significantly associated with poor DFS. Abstract : Supplemental digital content is available in the text.